EFEKTIVITAS PEMBELAJARAN FISIKA MENGGUNAKAN MODEL PEMBELAJARAN PDEODE DAN MODEL PBL TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMP NEGERI 5 KOTA TERNATE PADA MATERI KALOR - Sakinah Gay; Sumarni Sahjat; Fatma Hamid (Universitas Khairun, 2022)
This study aims to determine: 1) The effectiveness of the physics learning model using the PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) learning model and the PBL (Problem Based Learning) learning model on the physics learning outcomes of class VII students at SMP Negeri 5 Kota Ternate Academic Year 2021/2022. 2) Student activities on the implementation of the PDEODE learning model (Predict-Discuss-Explain-Observe-Discuss-Explain) and the Problem Based Learning (PBL) model on the physics learning outcomes of Class VII students of SMP Negeri 5 Ternate City for the 2021/2022 academic year. The type of research used is experimental and design research. The population in this study were class VII students who were in SMP Negeri 5 Ternate City, amounting to 130 spread over 5 classes and the sample in this study was part of the population, namely 26 students in class VII-4 as the experimental class I by applying the PDEODE learning model and 26 students of class VII-3 as experimental class II by applying the PBL learning model with the research design used is one-group pretest-posttest. The instrument used in this study was a multiple-choice test for cognitive learning outcomes and non-test in the form of student activity sheets. Data analysis used IBM SPSS 20.0, which is a parametric statistical test to test the hypothesis.